Mexican Hometown Associations in Chicagoacán : From Local to Transnational Civic Engagement - Bada, Xóchitl (Book collections on Project MUSE., 2014)
In this groundbreaking new book, Mexican Hometown Associations in Chicagoacán, Xóchitl Bada reveals how Mexican hometown associations, groups consisting of immigrants from the same small towns, have become a surprisingly powerful force for mobilizing social change in both the United States and Mexico. By giving voice to the members of a group of Chicago-based hometown associations from the state of Michoacán, Xóchitl Bada draws much larger conclusions about the emergence and global impact of new transnational forms of community activism.